PENGARUH KETINGGIAN TALANG DAN MEDIA TANAM SECARA HIDROPONIK VERTIKULTUR TERHADAP PERTUMBUHAN SELADA CHRIS GREEN (Lactuca sativa L.) - M. Nur; Ernita; Maizar; Oktafiani Agara (UIR Press, 2024)
The Effect of Hydroponic Height and Vertical Planting Media on the Growth of Chris Green (Lactuca sativa L.). This study was carried out at the Dokagu UIR Housing Block B No. 2, located in Air Dingin Village, Bukit Raya District, Pekanbaru City, from August to September 2022. A Split Plot Design (RPT) was employed for the experimental setup, with the height of the gutter (A) as the main plot and various types of planting media (B) functioning as subplots. The treatment combinations included four different levels of lettuce types and four levels of height positioning, resulting in 16 treatment combinations, each replicated three times, summing up to a total of 48 experimental units. The parameters measured were plant height, leaf count, wet weight, dry weight, and root volume. If the calculated F value exceeds the F table value, a further Honestly Significant Difference (HSD) test at the 5% significance level will be conducted. The findings revealed that the interaction between hydroponic height and planting media significantly affected all observed parameters, with the exception of plant dry weight. The most effective treatment combination was found to be a hydroponic height of 80 cm and cocopeat as the planting medium (A3B4). Moreover, hydroponic height had a significant effect on all measured parameters, with 80 cm (A3) yielding the best results. Additionally, the choice of planting medium significantly influenced all observed parameters, with cocopeat (B4) proving to be the best treatment.